A COMPARATIVE STUDY OF THE VERDICTS OF THE BUKITTINGGI RELIGIOUS COURT AND THE PADANG HIGH RELIGIOUS COURT ON CHILD CUSTODY FROM THE MASHLAHAH PERSPECTIVE - siadio, sidiq; Nofiardi, Nofiardi (UIN Mahmud Yunus Batusangkar, 2024)
Child custody disputes are common in Indonesia, particularly among public figures such as Virgoun and Inara, as well as Larissa Chou and Alvin Faiz. Economic instability, exacerbated by the Covid-19 pandemic, has significantly impacted mothers' ability to care for their children. In Minangkabau, the matrilineal system typically grants custody to the mother, as reflected in the PTA Padang decision, which contrasts with the ruling from PA Bukittinggi. Islamic law generally grants the mother the right to child maintenance after divorce until the child reaches the age of tamyiz. This study examines the child custody decisions of PA Bukittinggi and PTA Padang through the lens of mashlahah, assessing which ruling best serves the child's welfare. Using normative legal research methodology, the study analyzes primary data from PTA Padang Decision No. 62/Pdt.G/2022/PTA.Pdg, PA Bukittinggi Decision No. 621/Pdt.G/2022/PA.Bkt, and interviews with judges. The findings reveal significant differences in the legal reasoning and interpretation of the child’s best interests between the two courts.